Global marketing activities exposure and consumption behavior - Akhoundi, M.; Syuhaily Osman,; Nezakati, Hossein * (Lambert Academic Publishing, 2018)
Exposure to global marketing activities influences consumption behavior of consumers from any cultural layers including global, national, ethnic and individual. In a global market with a dynamic multi-level of culture, the roles of consumer individual values seems remarkable; as they are the nearest and the most unique cultural layer which individually affect consumer behavior. The study also integrated consumer ethnocentric tendency and domestic global brand attitude with the purpose of moderating of the effect of exposure to global marketing activities on consumption behavior. The behaviors studied in this research contain the consumption of global foods and drinks, personal care items, global clothing and accessories, household appliances, electronics, communications and luxury goods. Evidently, the product categories play significant roles in all relationships of the study